Chromobacterium violaceum infection in a domestic shorthaired cat with dog bite wounds - Zaini, Syamira Syazuana; Mohd Yusoff, Amal Amyrun; Chan, Wei Yee (Universiti Putra Malaysia Press, 2024)
Chromobacterium violaceum is a motile, facultative anaerobe and Gram-negative Bacillus, a common inhabitant of soil and water in tropical and subtropical regions. Chromobacterium violaceum is recognised as an opportunistic pathogen of humans and animals. Although rare, a few chromobacteriosis cases were reported in humans and several species of animals. However, there is no published report of Chromobacterium infection in cats. This report describes a C. violaceum infection in a cat with a history of non-healing dog bite wounds. The bacterial culture of the wounds revealed pure growth of C. violaceum on both aerobic and anaerobic cultures. The infection in this cat was successfully treated after changing the antibiotic to enrofloxacin based on an antibiotic sensitivity test (AST). This case demonstrates the importance of culture and AST tests in non-healing wounds. Chromobacteriosis can be included in the differentials, especially if wounds are contaminated by soil or stagnant water.